Therapeutic inertia in statin therapy for secondary prevention after percutaneous coronary intervention: a nationwide population-based cohort study - Young-Hoon Seo; Jee-Young Hong; Yong-Kyun Kim; Ki-Hong Kim; Taek-Geun Kwon; Jang-Ho Bae (BMC Cardiovascular Disorders)
Abstract Background Therapeutic inertia is defined as the failure to provide guideline-directed therapy and is a barrier to achieving optimal clinical outcomes. We aimed to evaluate therapeutic inertia in statin therapy after percutaneous coronary intervention (PCI) and its association with patient characteristics and physician’s prescribing practice. Methods We analyzed the medical claims data on patients undergoing PCI using National Health Insurance Service in Republic of Korea. The primary outcome of interest was therapeutic inertia, defined as not providing high-intensity statin (HIS) therapy within 30 days after discharge for PCI. To identify statin use in identical clinical setting, we restricted study duration to between 2013 American College of Cardiology/American Heart Association cholesterol guideline and publications of RACING (Randomized Comparison of Efficacy and Safety of Lipid-lowering with Statin Monotherapy Versus Statin–ezetimibe Combination for High-risk Cardiovascular Disease) and LODESTAR (Low-Density Lipoprotein Cholesterol-Targeting Statin Therapy Versus Intensity-Based Statin Therapy in Patients With Coronary Artery Disease) trials that demonstrated non-inferiority of alternative statin strategies compared with HIS therapy in atherosclerotic cardiovascular disease. We also assessed patient characteristics affecting HIS prescription, statin switching before and after PCI among previous statin users, and impact of previous statin regimen on prescribing of HIS. Results Of 204,708 participants (mean age 66.5 ± 11.3 years, 30.8% female, 56.6% previous statin users, 43.4% previous statin nonusers), therapeutic inertia was identified in 64.1%, and HIS prescription rate was higher in previous statin nonusers (42.0%) than in previous statin users (31.1%). There were few differences in patient characteristics as positive (male and acute coronary syndrome as indication for PCI) and negative (increase of age, comorbidities, and cardiovascular medications) predictors of HIS prescription between previous statin users and nonusers. Because 79.1% of previous HIS users and 23.8% of previous non-HIS users received HIS following PCI, previous HIS users were more likely to be prescribed HIS as compared to previous statin nonusers (odds ratio, 5.42; 95% confidence intervals, 4.44–6.61) and previous non-HIS users (odds ratio, 12.30; 95% confidence intervals, 9.95–15.19). Conclusions Suboptimal HIS prescription following PCI was substantially affected by patient characteristics and the practice of repetitive prescribing of previous statin without guideline-directed titration. Clinical trial number Not applicable.